CB1R-Mediated Activation of Caspase-3 Causes Epigenetic and Neurobehavioral Abnormalities in Postnatal Ethanol-Exposed Mice - Subbanna, Shivakumar; Nagre, Nagaraja N.; Shivakumar, Madhu; Joshi, Vikram; Psychoyos, Delphine; Kutlar, Abdullah; Umapathy, Nagavedi S.; Basavarajappa, Balapal S. (Frontiers in Molecular Neuroscience, 2018)
Alcohol exposure can affect brain development, leading to long-lasting behavioral problems, including cognitive impairment, which together is referred to as fetal alcohol spectrum disorder (FASD). However, the fundamental mechanisms through which this occurs are largely unknown. In this study, we report that the exposure of postnatal day 7 (P7) mice to ethanol activates caspase-3 via cannabinoid receptor type-1 (CB1R) in neonatal mice, and causes a reduction in methylated DNA binding protein (MeCP2) levels. The developmental expression of MeCP2 in mice is closely correlated with synaptogenesis and neuronal maturation. It was shown that ethanol treatment of P7 mice enhanced Mecp2 mRNA levels but reduced protein levels. The genetic deletion of CB1R prevented, and administration of a CB1R antagonist before ethanol treatment of P7 mice inhibited caspase-3 activation. Additionally, it reversed the loss of MeCP2 protein, cAMP response element binding protein (CREB) activation, and activity-regulated cytoskeleton-associated protein (Arc) expression. The inhibition of caspase-3 activity prior to ethanol administration prevented ethanol-induced loss of MeCP2, CREB activation, epigenetic regulation of Arc expression, long-term potentiation (LTP), spatial memory deficits and activity-dependent impairment of several signaling molecules, including MeCP2, in adult mice. Collectively, these results reveal that the ethanol-induced CB1R-mediated activation of caspase-3 degrades the MeCP2 protein in the P7 mouse brain and causes long-lasting neurobehavioral deficits in adult mice. This CB1R-mediated instability of MeCP2 during active synaptic maturation may disrupt synaptic circuit maturation and lead to neurobehavioral abnormalities, as observed in this animal model of FASD.